2013
DOI: 10.1016/j.jpedsurg.2012.09.027
|View full text |Cite
|
Sign up to set email alerts
|

The ACGME case log: General surgery resident experience in pediatric surgery

Abstract: Background General surgery (GS) residents in ACGME programs log cases performed during their residency. We reviewed designated pediatric surgery (PS) cases to assess for changes in performed cases over time. Methods The ACGME case logs for graduating GS residents were reviewed from academic year (AY) 1989–1990 to 2010–2011 for designated pediatric cases. Overall and designated PS cases were analyzed. Data were combined into five blocks: Period I (AY1989–90 to AY1993–94), Period II (AY1994–95 to AY1998–99), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 29 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…Manual recording is tedious and prone to inaccuracy. The literature on ACGME surgical resident case logs suggests underreporting when using manual submission, with only half of the residents surveyed recording major procedures and only 13 % logging minor procedures [15,16]. On the other hand, waiting for the semi-annual report may preclude proper intervention should a trainee fall behind case log minimum numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Manual recording is tedious and prone to inaccuracy. The literature on ACGME surgical resident case logs suggests underreporting when using manual submission, with only half of the residents surveyed recording major procedures and only 13 % logging minor procedures [15,16]. On the other hand, waiting for the semi-annual report may preclude proper intervention should a trainee fall behind case log minimum numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Findings show that the average pediatric surgery resident completes less than five and in some cases zero esophageal atresia repairs, choledochal cyst excisions, portoenterostomies, or resections of sacrococcyceal teratoma [7,8]. Of further concern is that general surgery residents, many of whom will care for children at significant geographic distance from major pediatric centers, seem to be doing fewer pediatric cases [9]. It is not known what factor is driving this trend, but the decline in operative exposure does not appear related to classified index cases, considered the domain of fellows or more senior trainees.…”
Section: Deliberate Practice In Surgical Educationmentioning
confidence: 99%
“…It is not known what factor is driving this trend, but the decline in operative exposure does not appear related to classified index cases, considered the domain of fellows or more senior trainees. Cases appropriate for a community institution such as inguinal and umbilical hernia repair dropped from 26.7 cases per North American general surgery resident to 18.5, a 30.7 % drop from the 1989-1990 academic year through 2007-2008 [9]. Since volume-outcome relationships are a well-described phenomenon across multiple surgical specialties, a drop in cases gives pause for concern.…”
Section: Deliberate Practice In Surgical Educationmentioning
confidence: 99%
“…8 There are limited reports of methods to facilitate GME programs providing objective performance measures to trainees. ACGME case logs have been developed for surgical residencies, [9][10][11] and to some extent, written experience logs have been described in primary care 12 and internal medicine. 13 Studies have shown that manual entry into case logs may only reflect 60% of true encounters.…”
Section: Introductionmentioning
confidence: 99%